Meningkatkan Kesadaran Masyarakat akan Pentingnya Protokol Kesehatan di Masa Pandemi - Afrizal Rahman; Rian Vebrianto; Musa Thahir; Desi Nori Sahputri (Anotero Lembaga Scientific Pekanbaru, 2021)
The implementation of the program increases public awareness of the importance of health protocols during the pandemic by providing a handwashing place at the Masjid Darul Jannah, this service aims to increase public awareness of the importance of health protocols during a pandemic, this is important because seeing the mosque is not available handwashing place at the door of the mosque the. This service was carried out with Participatory Action Research (PAR) on programs to increase public awareness of the importance of health protocols during the pandemic by providing a handwashing place at the Darul Jannah mosque which was held on July 21, 2021 at the Simpang Baru exit which involved 20 service participants. Data was taken using a questionnaire instrument (questionnaire) to determine the success/impression of the implementation of the service program. from the results of the analysis, it is known that the program increases public awareness of the importance of health protocols during the pandemic by providing a hand washing place which is considered successful, and the service participants strongly and agree with this service program. For this reason, it is hoped that all stakeholders in the village will support and carry out similar activities in different places so that information and knowledge as well as goodness, can be disseminated to many areas.